2017
DOI: 10.1111/jan.13506
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with continued smoking after treatment of oral cavity cancer: An age and survival time‐matched study

Abstract: People with oral cavity cancer were more likely to continue smoking after the treatment if they had low social support, depression, greater nicotine dependence and poor social-emotional function. Healthcare professionals should pay more attention to social support, psychological status and nicotine dependence of people who were treated for oral cavity cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The total score ranges from 0 to 100, with higher scores indicating higher levels of function and quality of life . The Chinese version of the UW‐QOL has acceptable reliability and validity . Cronbach's alpha of the study data was.82 (good) for the physical function scale and.87 (good) for the social‐emotional functional scale.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The total score ranges from 0 to 100, with higher scores indicating higher levels of function and quality of life . The Chinese version of the UW‐QOL has acceptable reliability and validity . Cronbach's alpha of the study data was.82 (good) for the physical function scale and.87 (good) for the social‐emotional functional scale.…”
Section: Methodsmentioning
confidence: 97%
“…Performance status was assessed using the Karnofsky Performance Status (KPS) Scale, which ranges from 0% to 100%, with 100% indicating normal function and 0% indicating death . The KPS has been widely used in studies of cancer patients …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of cancer patients in Taiwan indicated satisfactory psychometric properties for the UW‐QOL (ver. 4) . In this study, Cronbach's alpha was 0.84 for the physical subscale and 0.80 for the psychosocial subscale.…”
Section: Methodsmentioning
confidence: 48%
“…The KPS ranges from 0% to 100%, with 0% indicating death and 100% indicating completely normal function . The KPS has been widely used in studies of cancer patients …”
Section: Methodsmentioning
confidence: 99%